How Is Earnings Management Developing In Asia Pacific: A Scoping Review - Nurchita Arliza; Nurika Restuningdiah; Diana Tien Irafahmi (Asia Pacific Journal of Business Economics and Technology, 2023)
This study aims to map the development of earnings management research in the Asia Pacific. The scoping review method used in this study follows the protocol from Arksey and O'Malley (2005), which has five stages, namely (1) identifying research questions; (2) identifying relevant studies; (3) study selection; (4) creating data graphs; and (5) compiling, summarizing and reporting the results. The scope of this study uses 16 countries in the Asia Pacific with an observation period of 23 years (1998-2021). The sample of this study was 98 article data obtained from electronic database websites, namely Emerald Publish, Sage Journals, Science Direct, Springer, Taylor & Francis and Wiley. This mapping analysis shows that most of the research has been carried out in Malaysia, Australia and India. While Vietnam is the most minor area and requires further study and research related to earnings management. In addition, the governance structure consisting of institutional ownership, board of directors, CEO and audit committee is the most widely studied research. Meanwhile, cultural, language and religious factors still need to be studied. This research is expected to provide insights related to research that has yet to be covered and requires further research related to earnings management conducted in the Asia Pacific.